Synthesis of the Smallest Member of the Silylketene Family: H3SiC(H)=C=O. Issue 8 (7th March 2017) - Tarczay, György; Förstel, Marko; Góbi, Sándor; Maksyutenko, Pavlo; Kaiser, Ralf I.
Abstract: Exploiting photoionization reflectron time‐of‐flight mass spectrometry (PI‐ReTOF‐MS) combined with electronic structure calculations, it is shown that the hitherto elusive silylketene molecule (H3 SiC(H)=C=O)—the isovalent counterpart of the well‐known methylketene molecule—is forming via interaction of energetic electrons with low‐temperature silane–carbon monoxide ices. In combination with the infrared spectroscopically detected triplet dicarbon monoxide reactant, electronic structure calculations suggest that dicarbon monoxide reacts with silane via a de facto insertion of the terminal carbon atom into a silicon–hydrogen single bond. This is followed by non‐adiabatic reaction dynamics triggered by the heavy silicon atom intersystem crossing from the triplet to the singlet manifold, eventually leading to the formation of silylketene. The non‐equilibrium nature of the elementary reactions within the exposed ices results in an exciting and novel chemistry which cannot be explored via traditional preparative chemistry. Since the replacement of hydrogen in silane can introduce side groups such as silyl or alkyl, the reaction of triplet dicarbon monoxide with silane represents the parent system for a previously disregarded reaction class revealing an elegant path to access the largely reactive group of silylketenes. Abstract : Smallest silylketene : Photoionization reflectron time‐of‐flight mass spectrometric (PI‐ReTOF‐MS) and infrared spectroscopic methods were applied to detect the hitherto elusive silylketene molecule (H3 SiC(H)=C=O). Silylketene is formed via interaction of energetic electrons with low‐temperature silane–carbon monoxide ices. Ab initio computations were used both to support the identification of silylketene and to explore its formation mechanism.